Factors associated with acceptability of circumcision among male drug users in western China: a cross-sectional study. (July 2013) - Huang, J; Jiang, J; Abdullah, A S; Yang, X; Wei, B; Deng, W; Qin, B; Upur, H; Zhong, C; Wang, Q; Wang, Q; Ruan, Y; et al.
This study is aimed to investigate whether male circumcision (MC) is feasible among IDUs in China. 1304 drug users who attended methadone maintenance therapy clinics in Guangxi, Chongqing and Xinjiang were selected for participation by using convenience sampling, and completed a self-administered questionnaire. The factors associated with the acceptability of MC were examined via multiple logistic regression models. 45.2% (589/1304) of the participants reported an acceptance of MC. Many of the participants who were initially not willing to accept MC (715/1304) had changed their mind when they were informed that MC would reduce the risk of HIV and STDs (43.4%; 310/715), that MC is associated with few surgery-related complications (23.1%; 165/715), that the surgical procedure could be arranged free of charge (20.1%, 144/715). In the multivariate analysis, higher acceptability of MC was associated with knowledge of the hazards of phimosis (OR=2.22), the presence of phimosis (OR=14.87), and knowledge that MC can prevent AIDS and STDs (OR=1.49); while lower acceptability was associated with residing in Chongqing province (OR=0.41) and an educational level of junior (OR=0.64) and senior high (OR=0.63) school. The MC policy targeting IDUs in China should take into account these factors associated with MC acceptability.